EDUKASI DAN SIMULASI PENGGUNAAN APE MATEMATIKA AUD UNTUK GURU DAN ORANG TUA - Rohyana Fitriani (UNIVERSITAS PGRI MADIUN, 2022)
The essence of mathematics is a formal deductive axiomatic system. As an axiomatic system, mathematics contains components and rules of composition or work that can establish functional relationships between components and it is systematic. The success of individual mathematical abilities is greatly influenced by their mastery of mathematics from the very beginning. Therefore, children from an early age need to be introduced to mathematics, cultivate and experience mathematics as part of their life. It is necessary to introduce mathematics through real / concrete activities, games and of course using interesting educational play tools. So that the team held community service, namely education and simulation of the use of AUD math APE for teachers and parents in PAUD Dahlia so that by holding APE mathematics education and simulations can provide an overview and knowledge to teachers and parents to be able to create and use simple and easy to obtain APE namely from used goods. Teachers and parents do not have to buy because they can use used goods to make APE in developing early childhood mathematics